The identification of cutin synthase: formation of the plant polyester cutin - Yeats, Trevor H. (2012)
A hydrophobic cuticle consisting of waxes and the polyester cutin covers the aerial epidermis of all land plants, providing essential protection from desiccation and other stresses. We have determined the enzymatic basis of cutin polymerization through characterization of a tomato extracellular acyltransferase, CD1, and its substrate, 2-mono(10,16-dihydroxyhexadecanoyl)glycerol (2-MHG). CD1 has in vitro polyester synthesis activity and is required for cutin accumulation in vivo, indicating that it is a cutin synthase.